Strategy to Improve Employee Security Awareness at Information Technology Directorate Bank XYZ - Halida Ernita; Yova Ruldeviyani; Desiana Nurul Maftuhah; Rahmad Mulyadi (Ikatan Ahli Informatika Indonesia (IAII), 2022)
Bank handles private information like customer financial transactions and personal data. There was a 63% increase in cyberattacks attempted against Bank XYZ in 2021, and 1,323 attempted attacks on corporate email Bank XYZ. Therefore, implementing security awareness training for all employees is crucial for Bank XYZ. The information security awareness program must be assessed to determine the program's efficiency and the level of information security awareness among employees. Therefore, this study assesses the information security awareness at Bank XYZ, especially the Information Technology (IT) Directorate using the Human Aspect of Information Security Questionnaire (HAIS-Q) method. The findings of this study revealed that employees at Bank XYZ in the information security work unit had a